Práticas de gestão estratégica de custos adotadas por empresas brasileiras - Muniz, Luciani da Silva (Universidade do Vale do Rio dos Sinos, 2010)
This study investigates the adoption of practices of large Brazilian companies? Strategic Management Accounting (SMA). There is a vast literature about the topic, highlighting its importance for companies to achieve competitive advantage and about their permanency in the market in a continuous and sustainable manner. The research selected 15 practices highlighted by the authors as being the mainly ones. The survey data (characterized as descriptive and applied research) were obtained through structured questionnaire posted on the internet, which obtained 54 returns of companies inside the group of the 500 largest companies according to the publication of the Revista Exame of 2008. Data analysis was carried out through descriptive statistics and by the use of Neural Networks. It was found that the most of the companies use the cost target, pattern and determinants of cost; it was not possible identify according to the answers of the firms the intention to use another practice in the future. It was analysed the adoption of the practice found in relation to benefit or to perceived difficulty, being this criteria related to the adoption or not adoption of a particular practice of SMA. It is also possible to relate this study to other international studies and notice similarities between the main practices adopted by Brazilian companies and the international ones.
Keywords: Gestão estratégica de custos; Práticas de gestão estratégica de custos; Competitividade; Vantagem competitiva; Strategic cost management; Competitiveness; Practice of strategic cost management; Competitive advantage; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis